The vertical distribution of fish on two offshore oil platforms - Tothill, Thomas; Meeuwig, Jessica J.; van Elden, Sean (Frontiers in Marine Science, 2024)
For full guidelines please refer to Author Guidelines Knowledge of platform ecology is necessary to best inform decommissioning practice. Remotely operated vehicle (ROV) video is often collected during standard industry operations and may provide insight into the marine life associating with offshore platforms, however, the utility of this video for ecological assessments remains unclear. Archival ROV video surveys at the Wandoo oil platforms on Australia's North West Shelf was evaluated for its utility, with only 4.9% of imagery usable for standardised ecological studies. Based on the subset of usable ROV video, the influence of depth and structural complexity on attributes of the fish assemblage on the Wandoo oil platforms was examined. Vertical ROV transects on three vertical shafts on the Wandoo platforms were stratified into 10 m depth strata from 0 to 50 m, with 111 fish taxa from 25 families identified and counted across all depth strata. Across allAt both platforms, taxonomic richness and abundance was significantly highest in shallow regions and declined with depth. Small reef fish were predominantly associated with structurally complex habitat in shallow regions (<22 m), whilst large demersal species dominated below 32 m. Future decommissioning policy in Australia should consider the vertical fish distributions and the importance of shallow sections of platforms. Finally, the dearth of usable video was due to the haphazard method of collection and it is recommended that future surveys should be conducted according to scientific standards to ensure greater utility of the video for both industry use and scientific research. conduct standardised transects in high definition video at constant speeds and orientations.